A microporous chromium-organic framework fabricated via solvent-assisted metal metathesis for C2H2/CO2 separation. Issue 31 (13th July 2022) - Lu, Ting-Ting; Fan, Ying-Yi; Wang, Xiao-Ning; Wang, Qiang; Li, Bao
Abstract : An iso-structural Cr-MOF has been constructed based on one novel Fe-MOF by post-synthetic metalation, which exhibits potential C2 H2 separation ability from CO2 and C2 H4 . Abstract : Removal of CO2 or C2 H4 from C2 H2 is still a challenging task due to their similar physical–chemical properties. Here, a bifunctional ligand decorated with amino and sulfoxide groups, 5′, 5′′′′-sulfonylbis (2′-amino-[1, 1′:3′, 1′′-terphenyl]-4, 4′′-dicarboxylic acid) (H4 L), was employed to construct a new microporous iron-organic framework (Fe-MOF) with the formula [(Fe3 O)(L)1.5 (H2 O)3 ] n . This MOF can serve as a parent structure to obtain the isostructural Cr-MOF by solvent-assisted metal metathesis. Furthermore, the gas adsorption and separation performance of these two MOFs were systematically investigated. Compared to Fe-MOF, Cr-MOF shows a moderately higher CO2, C2 H2 and C2 H4 uptake capacity. Additionally, Cr-MOF can selectively adsorb C2 H2 over CO2 and C2 H4 . The separation potential towards C2 H2 /C2 H4 and C2 H2 /CO2 was further established via IAST calculations of mixture adsorption equilibrium. IAST selectivity values of Cr-MOF are 3.4 for C2 H2 /C2 H4 and 6.9 for C2 H2 /CO2 at 298 K and initial pressure, indicating its potential C2 H2 separation ability.